2019
DOI: 10.1038/s41419-019-1525-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide: a gaseous signaling molecule modulates tissue homeostasis: implications in ophthalmic diseases

Abstract: Hydrogen sulfide (H 2 S) serves as a gasotransmitter in the regulation of organ development and maintenance of homeostasis in tissues. Its abnormal levels are associated with multiple human diseases, such as neurodegenerative disease, myocardial injury, and ophthalmic diseases. Excessive exposure to H 2 S could lead to cellular toxicity, orchestrate pathological process, and increase the risk of various diseases. Interestingly, under physiological status, H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 164 publications
0
36
0
Order By: Relevance
“…We also identified factors and pathways contributing to H 2 S toxicity to the human cornea. In the eye, low endogenous quantities of H 2 S have beneficial effects 20,[25][26][27][28][29][30][31][32] but high H 2 S levels have toxicological effects. 10,13,[33][34][35] The utilized toxicological assays demonstrated that H 2 S toxicity to hCSFs is dose and time dependent (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also identified factors and pathways contributing to H 2 S toxicity to the human cornea. In the eye, low endogenous quantities of H 2 S have beneficial effects 20,[25][26][27][28][29][30][31][32] but high H 2 S levels have toxicological effects. 10,13,[33][34][35] The utilized toxicological assays demonstrated that H 2 S toxicity to hCSFs is dose and time dependent (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium hydrosulfide (NaSH) (Sigma-Aldrich) powder, which produces H 2 S gas after addition to media, was used for studying H 2 S-induced toxicity. 20,21 The hCSFs were grown in T25 tissue culture flasks to 80-85% confluence and were treated with different concentrations of NaSH (1-10 mM) in a serum-free environment for up to 72 hours. Immediately after adding NaSH, the T25 culture flasks were sealed with plug-seal caps to prevent the leakage of H 2 S gas.…”
Section: Primary Hcsfs and Nash Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen sulfide (H 2 S) is a newly discovered gas signal molecule which is generated in the human body [68]. Low concentration of H 2 S plays a role in relaxing blood vessels, controlling blood pressure and maintaining homeostasis [69,70].…”
Section: Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%